Impact of transcatheter aortic valve implantations on temporal trends of pacemaker implantations among French octogenarians: a nation-wide cohort study over the period 2008–2018. (14th October 2021) - Jacob, S; Van Rothen, J; Combes, S; Errahmani, M.Y; Cardin, C; Combes, N; Albenque, J.P; Boveda, S
Abstract: Background: The indications for permanent pacemaker implantation (PPMI) are strongly associated with age, with the highest rates for octogenarians (>80 years old). Over the last decade, impact of aging on temporal trends in PPMI rates among octogenarians is questionable. In the 2010's, transcatheter aortic valve implantation (TAVI) has emerged for inoperable or high-risk patients, mainly octogenarians, with an exponential increase over years. PPMI is a common short-term complication after TAVI procedure. Many studies have explored these post-TAVI PPMI in terms of incidence, timing and outcomes of PPMI following TAVI, but there are no data on the impact of TAVI on PPMI temporal trend at a nationwide scale. Purpose: To evaluate whether PPMI in octogenarians have increased during the last decade, independently from age and sex, on a nationwide scale. Eventually, to estimate the potential contribution of TAVI in PPMI increase in this setting. Methods: Our study was based on octogenarians from the Echantillon Généraliste de Bénéficiaires, the 1/97 random sample of the French nationwide health insurance claims database. Between 2008 and 2018, we identified de novo PPMI and TAVI with medical procedures codes in the French Common Classification of Medical Procedures (CCAM). Annual incidence rates of PPMI were evaluated between 2008 and 2012 (preTAVI-period). The number of observed PPMI cases, O, in the period 2013–2018 (TAVI-period) was compared with the expected number of PPMI cases, E, calculated by using 2008–2012 incidence rates with age and sex standardization. We then computed the standardized incidence ratio (SIR) of the observed number of PPMI to the expected number of PPMI (O/E), with 95% confidence intervals (CIs). Thereafter, we evaluated the contribution of post-TAVI PPMI in the number of excess cases of PPMI (O-E) for the period 2013–2018. Results: The population of octogenarians increased from 23, 822 in 2008 to 33, 752 in 2018. In 2008, 130 PPMI were observed (546/100, 000 inhabitants) reaching 228 PPMI (676/100, 000) in 2018 with a marked increase in rates from the year 2012. During the period 2013–2018, for all octogenarians, 1242 cases of PPMI were observed, compared with 1171.3 expected cases of PPMI, corresponding to a significant SIR=1.06 (95% CI: 1.01–1.12). For the subpopulation of octogenarians without TAVI, no excess risk was observed with a SIR=1.01 (95% CI: 0.95–1.06). Among the excess cases of PPMI observed in 2013–2018 in all octogenarians, 72% were post-TAVI PPMI. Conclusion: Based on our study, the number of observed PPMI in octogenarians in period 2013–2018 is 6% higher than the number we would expect. Nearly three-quarter of these excess cases are attributable to TAVI complication. Funding Acknowledgement: Type of funding sources: None.